المنهج الدعوي للشيخ أبو بكر جابر الجزائري من خلاله رسائله - وقادي نصر (University of Eloued جامعة الوادي, 2024)
تناولت الدراسة الحالية المنهج الدعوي للشيخ أبي بكر جابر الجزائري من خلال رسائله الدعوية، وإشكالية هذه الدراسة هي: من هو أبو بكر الجزائري وما منهجه الدعوي المتمثل في رسائله؟ وقد قسم البحث إلى أربعة مباحث، تناول المبحث الأول سيرته الذاتية، وخصص الثاني لأسس الوعظ وآداب الخطباء، أما المبحث الثالث فقد تناول نشاطه الإصلاحي داخل الجزائر وخارجها، أما المبحث الأخير فقد تناول المنهج الدعوي للشيخ للمسلمين وغير المسلمين. وأخيراً ختم البحث ببيان أهم النتائج التي توصلت إليها من بداية الموضوع إلى نهايته."The current study dealt with The preaching approach of Sheikh Abu Bakr Jaber Al- through his preaching messages.through his preaching messages. The poblematic of this study is as follows: Who is Abu Bakr Al-Jazairi and what is his preaching approach represented in his messages? The research is divided into four sections. The first section discusses his biography. The second is devoted to the foundations of preaching and the etiquette of preachers. Whereas, the third dealt with his reformist activity inside and outside Algeria. the last section treats the preaching approach of Cheikh for Muslims and non-Muslims. Finally, the research is concluded by stating the most important findings I reached from the beginning of the topic to its end. "
Keywords: المنهج الدعوي، أبو بكر الجزائري، الرسائل.; The implementation of the call; Abu Bakr Al-Jazaery; letters.